2021
DOI: 10.3390/molecules26206238
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Role of Berberine, an Isoquinoline Alkaloid, on NLRP3 Inflammasome Activation for the Treatment of Inflammatory Diseases

Abstract: The pyrin domain-containing multiprotein complex NLRP3 inflammasome, consisting of the NLRP3 protein, ASC adaptor, and procaspase-1, plays a vital role in the pathophysiology of several inflammatory disorders, including neurological and metabolic disorders, chronic inflammatory diseases, and cancer. Several phytochemicals act as promising anti-inflammatory agents and are usually regarded to have potential applications as complementary or alternative therapeutic agents against chronic inflammatory disorders. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
3
0
1
Order By: Relevance
“…Berberine (BBR), a natural isoquinoline alkaloid isolated from several traditional Chinese herbal plants, is traditionally used to treat diarrhea and gastroenteritis [ 28 , 37 ], and it was reported to inhibit the activation of the NLRP3 inflammasome [ 38 ]. Here, we intended to investigate whether BBR could inhibit NLRP3 inflammasome activation caused by HuNoV and found that BBR treatment reduced the secretion of IL-1β and IL-18 and suppressed N-GSDMD-driven pyroptosis through inhibiting the activation of NLRP3 inflammasome caused by HuNoV and P22, suggesting that BBR has the potential to treat HuNoV-induced acute gastroenteritis through inhibiting the inflammatory response and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (BBR), a natural isoquinoline alkaloid isolated from several traditional Chinese herbal plants, is traditionally used to treat diarrhea and gastroenteritis [ 28 , 37 ], and it was reported to inhibit the activation of the NLRP3 inflammasome [ 38 ]. Here, we intended to investigate whether BBR could inhibit NLRP3 inflammasome activation caused by HuNoV and found that BBR treatment reduced the secretion of IL-1β and IL-18 and suppressed N-GSDMD-driven pyroptosis through inhibiting the activation of NLRP3 inflammasome caused by HuNoV and P22, suggesting that BBR has the potential to treat HuNoV-induced acute gastroenteritis through inhibiting the inflammatory response and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine also inhibited AMPK-dependent autophagy in adipose tissue macrophages, which reduced palmitate-induced inflammasome activation, IL-1β release, insulin resistance ( 125 ). Beneficial effects of berberine-mediated inflammasome inhibition have been reported in Parkinson’s disease, endovascular injury, drug-induced hepatotoxicity and diabetic nephropathy (by suppressing epithelial to mesenchymal transition (EMT) ( 126 ). Given the inhibitory effects of berberine on inflammasome activation and the importance of this pathway in radiation-induced injury, we propose that berberine may protect patients from radiation-induced lung and abdominal injury ( 112 , 113 ) by inflammasome inhibition.…”
Section: Berberinementioning
confidence: 99%
“…图 2 小檗碱对典型炎症通路的抑制作用 Figure 2 Inhibitory effect of berberine on canonical inflammatory pathways 2.2 NLRP3 炎性小体 NLRP3 (NOD-, LRR-, and pyrin-domain containing protein 3)是一种多蛋白复合物 [37] : [38] . NLRP3 作为目前研究最为广泛的炎 性小体, 其确切的下游抗炎机制尚未完全发掘, 其抑制 剂仍处于临床, 有待进一步探索 [39] .…”
Section: Nf-κb 信号通路unclassified